1985
DOI: 10.1364/josaa.2.000891
|View full text |Cite
|
Sign up to set email alerts
|

Line integrals and physical optics Part I The transformation of the solid-angle surface integral to a line integral

Abstract: The surface integral that measures the solid angle subtended by a planar aperture at a point in space is transformed to a line integral over the boundary of the aperture. The problem is divided into three distinct cases, and in each case a transformation is established. The results have a direct application to the problem of converting the Kirchhoff integral of diffraction by an aperture on a plane screen to a line integral over the rim of the aperture. gan Radiation Laboratory, the Techniis engage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…By extending the work by Asvestas [4]- [6], the traditional surface integral of the electric physical optics (PO) scattered field from a perfectly electrically conducting (PEC) planar plate illuminated by an electric Hertzian dipole was cast into a line integral along the edges of the plate in [7]. The procedure of [7] was recently extended in [8] to derive a line integral representation of the electric PO scattered field from a penetrable planar plate illuminated by a plane wave.…”
Section: Introductionmentioning
confidence: 89%
“…By extending the work by Asvestas [4]- [6], the traditional surface integral of the electric physical optics (PO) scattered field from a perfectly electrically conducting (PEC) planar plate illuminated by an electric Hertzian dipole was cast into a line integral along the edges of the plate in [7]. The procedure of [7] was recently extended in [8] to derive a line integral representation of the electric PO scattered field from a penetrable planar plate illuminated by a plane wave.…”
Section: Introductionmentioning
confidence: 89%
“…However, such an indubitable computational advantage is balanced by the presence of singularities in the integrand of the one-dimensional BDW integral, which gives numerical problems, especially whenever the BDW field has to be evaluated close to the geometrical shadow at the observation plane [8]. To overcome such difficulties, important modifications to the BDW theory were provided by several authors [9][10][11][12][13][14][15]. In 2000, Hannay [16] showed that, when the BDW integral (for spherical or plane wave illumination) is written within paraxial approximation, it takes on a mathematical form in which the above singularities are no longer present.…”
Section: Introductionmentioning
confidence: 99%
“…The present work was inspired by the three papers by Asvestas [13], [15], [16]. Asvestas [13] considered the electromagnetic diffraction by an aperture in a perfectly conducting plane screen and took as his starting point the Kirchhoff diffraction integral for electromagnetic fields as derived by Kottler [17].…”
Section: I Introductionmentioning
confidence: 99%